THE INNOVATIVE FORMS IN THE ACTIVITY OF REGIONAL ART MUSEUM OF VINNYTSIA AS THE IMPORTANT REGIONAL CENTER OF CULTURE AND EDUCATION - Sidletska, Tetiana; Kniazieva, Tetiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article has revealed and founded the innovative forms in the activity of Regional Art Museum of Vinnytsia. The research methodology is based on the systemic, structural, functional and active approaches. It makes possible to analyze the development and functions of Regional Art Museum of Vinnytsia, to determine the main directions, types of work and innovative forms of the museum activity as well as to show the role and significance of such important regional cultural and educational establishment. It is admitted that due to the introduction of innovative forms and modern technologies the museum has transformed its activity and has remained relevant to the contemporary audiences